2016
DOI: 10.1080/10715762.2016.1202407
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum arginase I and l-arginine or exhaled nitric oxide in asthma

Abstract: The relationship between serum arginase I and serum l-arginine or fractional exhaled nitric oxide (FENO) was evaluated cross-sectionally in asthmatic patients. No sex difference was observed in the serum mean levels of arginase I and l-arginine or FENO. Arginase I and FENO were higher in patients 60 or younger years than in those over 60 years. Asthmatic patients were divided into three groups: no steroid therapy, inhalation steroid therapy, and oral steroid therapy. Arginase I, FENO and high-sensitivity-C-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…For instance, men have been found to have higher FeNO than women in studies of healthy13 and asthma participants 14. Advanced age has been associated with higher ADMA levels in studies of individuals with15 and without asthma 16 17. Studies of L-arginine metabolism and race have revealed conflicting results in populations without asthma with respect to ADMA 18–20.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, men have been found to have higher FeNO than women in studies of healthy13 and asthma participants 14. Advanced age has been associated with higher ADMA levels in studies of individuals with15 and without asthma 16 17. Studies of L-arginine metabolism and race have revealed conflicting results in populations without asthma with respect to ADMA 18–20.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, neither ICS use, nor specifically the dose used, was associated with any clinically meaningful risk changes for cancer, although some risk estimates had low p -values. Lowering chronic inflammation may decrease the risk of cancer [ 11 , 13 , 14 , 15 , 16 , 17 , 18 ], and thus the more frequent use of oral and inhaled corticosteroids in patients with asthma-COPD overlap may have decreased their risk of cancer events by lowering chronic inflammation. Since our results were neutral, taken together, this could be caused, at least in part, by “neutralization” of a possible increased risk of cancer events in the asthma-COPD overlap patients on one side, and a protective effect of oral corticosteroids and ICS in the same groups of patients on the other side.…”
Section: Discussionmentioning
confidence: 99%
“…The sub-study was based on the CANTOS randomized controlled trial, which examined 10,061 patients with previous myocardial infarction and an elevated level of hsCRP, to see if inhibition of Interleukin-1-beta driven inflammation could reduce the risk of cardiovascular events [ 12 ]. Similarly, cohort studies have pointed towards a cancer-protective effect of ICS, which has also been shown to lower hsCRP in patients with asthma [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%